Coping Mechanisms in Schizophrenia Patients: Concept Analysis - Asriyani Asriyani; Darti Darti; Muliani Muliani; Ratna Sari Putri; Sudarwati Safwan; Satriya Pranata; Siti Aisah; Aric Vranada (Indonesian Journal of Global Health Research, 2024)
Coping mechanisms greatly help schizophrenia patients deal with psychotic symptoms such as hallucinations, delusions, and disorganized thoughts, as well as manage the emotional and social effects of their illness. The purpose of this concept analysis is to gain a more detailed and in-depth understanding of the use of coping mechanisms as part of schizophrenia therapy. This concept analysis uses the Walker and Avant approach with relevant literature findings related to the concept were obtained through concept databases such as Google Scholar, PubMed, Scopus, etc. Keywords used in the literature search include "Coping mechanisms", and "Scizophrenia". The inclusion criteria for articles were articles written in English and Indonesian, full text, and articles published in the last 5 years from 2019-2024 and open access as many as 7 articles. The results Adaptive coping mechanisms, such as problem solving and seeking social support, can help patients deal with stress, reduce symptoms, and improve their quality of life. Conversely, maladaptive coping strategies, such as avoidance or denial, actually risk worsening the patient's condition, increasing social isolation, and increasing the likelihood of symptom recurrence. It is hoped that more in-depth education about effective coping mechanisms needs to be included in nurse training and patient counseling.